A DESCRIPTIVE STUDY OF ISOTONIC DRINK SPONSORSHIP FOR RUNNING COMMUNITIES IN INDONESIA, CASE STUDY : POCARI SWEAT AND BR20 RUNNING COMMUNITY - Basri, Muhammad Rizki; Iskandar, Budi Permadi (Journal of Business and Management, 2017)
Abstract. In current times, running sport take the interest of the people of Indonesia, the development of this running sport led to the emergance of running communities. Beginning with the emergence of Indorunners running community in Jakarta in 2009, to develop to other area. One of the running community in the city of Bandung is BR20. BR20 was formed in 2012 in Bandung city, West Java. This community is used as a gathering place, to share stories, to find friends to run, or to show their social status. The emergence of this running community attracts companies, especially those relating to running sports, to promote their products by sponsoring running communities. Pocari Sweat as one of the packaging isotonic beverage products participates to enliven the running sport in Indonesia. Pocari Sweat gave sponsorship to BR20 community. Pocari Sweat as a party that gives sponsorship certainly has a certain hope for the running community and how the relationship with the community run BR20 can be formed. The purpose of this study is to explain the expectations of Pocari Sweat in sponsoring the running community, Acknowledge actual feedback from the running community against Pocari Sweat, and acknowledge the relation between Pocari Sweat and BR20 running community. The author will use the method of qualitative analysis, by conducting interviews and field observations. The results of this thesis show that Pocari Sweat can achieve the desired expectations, the community provides space for Pocari Sweat, and good relationship with the community run with two-way communication.Â Keywords: community, running community, sponsorship, sponsors relationship, sponsorship expectation